2022
DOI: 10.1002/tcr.202200070
|View full text |Cite
|
Sign up to set email alerts
|

The Perfect Imperfections in Electrocatalysts

Abstract: Modern day electrochemical devices find applications in a wide range of industrial sectors, from consumer electronics, renewable energy management to pollution control by electric vehicles and reduction of greenhouse gas. There has been a surge of diverse electrochemical systems which are to be scaled up from the lab‐scale to industry sectors. To achieve the targets, the electrocatalysts are continuously upgraded to meet the required device efficiency at a low cost, increased lifetime and performance. An atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“… , Although pure Ni­(OH) 2 exhibits a poor NitRR performance (low NH 3 FE and yield rate), the generation of a small amount of in situ formed Ni­(OH) 2 under the alkaline media could also enhance the water adsorption and dissociation step, thus supplying necessary protons to the electrophilic single-atom site and indirectly improving the NitRR performance of the Gd SA -D-NiO 400 (Figure S37). , More importantly, post stability characterizations (XRD, HAADF-STEM, EDS, XPS, and FT-EXAFS) revealed that the structure and electrophilic nature of the Gd SA sites were well maintained after the cycling test, further attesting to their superior chemical stability (Figure S38). …”
Section: Resultsmentioning
confidence: 99%
“… , Although pure Ni­(OH) 2 exhibits a poor NitRR performance (low NH 3 FE and yield rate), the generation of a small amount of in situ formed Ni­(OH) 2 under the alkaline media could also enhance the water adsorption and dissociation step, thus supplying necessary protons to the electrophilic single-atom site and indirectly improving the NitRR performance of the Gd SA -D-NiO 400 (Figure S37). , More importantly, post stability characterizations (XRD, HAADF-STEM, EDS, XPS, and FT-EXAFS) revealed that the structure and electrophilic nature of the Gd SA sites were well maintained after the cycling test, further attesting to their superior chemical stability (Figure S38). …”
Section: Resultsmentioning
confidence: 99%
“…This interface is consequential in determining the inter-lattice charge transfer and electronic environment of the active center that in turn relies on the neighboring atomic sites. 26 Because of the 2D wrapped 1D morphology, the 87 ± 21 nm diameter of the CoP NWs (Fig. S4a-c †) increases to 101 ± 24 nm for NV-21-CP (Fig.…”
Section: Nv-xy-cop/cc Systemmentioning
confidence: 97%
“…8,18,28 Herein, we reasoned that excessive amounts of a secondary element doping may lead to its accumulation and phase separation, affording abundant heterogeneous interfaces. 29,30 The strain regions arising from heterogeneous interfaces can regulate the conductivity, mechanical strength, plasticity, charge transfer properties and electron density of the catalysts, which could further affect the behaviors of electrochemical redox processes. 30 Based on this hypothesis, we fabricated a series of NiRu-based electrocatalysts with multi-active sites through a convenient and rapid microwave method.…”
Section: Introductionmentioning
confidence: 99%